Factors affecting the attraction of Prorops nasuta Waterston (Hymenoptera: Bathylidae) to odors emitted by dust/frass of its host, the coffee berry borer. - López-Rodríguez, Marta Aremi Aremi; Chiu-Alvarado, Pilar; C. Rojas, Julio (Instituto de Ecología, A.C., 2009)
The parasitoid Prorops nasuta Waterston (Hymenoptera: Bathylidae) is a wasp that feeds upon and parasitizes the coffee berry borer, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae), which is the most important pest of coffee (Coffea spp.) in the world. Previous studies have shown that P. nasuta females are attracted to the odors emitted by dust/frass of H. hampei. In this study, the effect of age, feeding status, sex and previous experience of P. nasuta on female attraction to the dust/frass odors was investigated in the laboratory using a Y-tube olfactometer. Females without food and those fed with a solution of honey-water (1: 1) significantly preferred dust/frass odors over clean air. In contrast, females fed with H. hampei immature stages did not show any preference for dust/frass odors or clean air. Female age did not influence the attraction of P. nasuta to dust/frass odors. P. nasuta males were not attracted to dust/frass odors. Both naïve and experienced females were similarly attracted to dust/frass odors, suggesting that the response of P. nasuta to dust/frass odors is innate.